HIPERHOMOSISTEINEMIA SEBAGAI RISIKO PENYAKIT JANTUNG KORONER - Astoni, Muhamad Ayus; Irawan, Bambang (Fakultas Kedokteran Universitas Brawijaya, 2005)
The elevation of total plasma homocysteine is associated with increase of risk for cardiovascular disease, cerebrovascular disease, and atherothrombosis in peripheral arteries. Several prospective and retrospective studies had conformed the positive association between hyperhomocysteinemia and risk for cardiovascular disease. However, it whether hyperhomocysteinemia is an independent riskfactor for cardiovascular disease associated with the others risk factors still become a question. The aim of this study was to identify the association between hyperhomocysteinemia and increased risk for cardiovascular disease. A matched case-control study based on 50 consecutive adult patients aged more than 18 years old who admitted in Dr. SardjitoGeneral Hospital by first acute coronary syndrome.Fifty comparison control subjects were randomly selected age and gender group-matched patients admitted caused by conditions other than cardiovascular disease to the same hospital. Each case was enrolled, and comparison subject was randomly selected. Fasting blood samples for homocysteine were obtained from both groups. Chi square test, McNemar chi square test, and independent t test had been used in univariate analysis. Confounding factors had been analysed using